The Role of Guidance and Counseling Teachers in Addressing Juvenile Delinquency in Indonesian Schools - Sugeng Sejati (JPI: Jurnal Pustaka Indonesia, 2023)
Adolescence is widely recognized as a critical developmental stage often associated with vulnerability to deviant behaviors, particularly when social and educational environments fail to provide adequate guidance. This study aims to examine the role of guidance and counseling teachers in addressing juvenile delinquency in Indonesian schools through a comprehensive library research approach. Data were collected and analyzed from scholarly articles, books, reports, and official documents using thematic content analysis to identify types, causes, and consequences of juvenile delinquency, as well as effective counseling interventions. The findings reveal that juvenile delinquency commonly manifests in four categories: acts causing physical harm, material losses, social deviance, and status-related violations, which are strongly influenced by family disharmony, peer pressure, weak self-control, and exposure to negative media. Guidance and counseling teachers play a pivotal role through preventive strategies (information services, group guidance, mediation), repressive measures (home visits, individual and group counseling), and curative approaches (case conferences, case referrals). These interventions not only mitigate immediate behavioral problems but also foster resilience, positive identity development, and academic engagement among students. The study contributes to the literature by emphasizing the underexplored role of school-based counseling in the Indonesian context and highlights its significance in shaping character education and preventing long-term social maladjustment. The findings imply that strengthening the capacity and recognition of school counselors is essential for sustainable educational development and for reducing youth delinquency rates in Indonesia and comparable settings.